A 70 Ma record of suprasolidus conditions in the large, hot, long‐duration Grenville Orogen. (10th April 2018) - Turlin, François; Deruy, Clara; Eglinger, Aurélien; Vanderhaeghe, Olivier; André‐Mayer, Anne‐Sylvie; Poujol, Marc; Moukhsil, Abdelali; Solgadi, Fabien
Abstract: Petrochronology of magmatic monazite and apatite from a single paragneiss leucosome derived by in situ partial melting documents the thermal evolution of the Allochthonous Belt of the central Grenville Province. Monazite records suprasolidus metamorphism from ca. 1080 to 1020 Ma under high temperature up to 850°C. Apatite from the same leucosome yields an age of 960 Ma, consistent with cooling of this crustal segment down to subsolidus conditions of ca. 450°C. A pegmatitic granite dyke, with lobate contacts, previously dated at ca. 1005 Ma (Turlin et al., 2017 ) is interpreted to intrude the paragneisses at a temperature of ca. 650°C close to the wet‐solidus. These data document slow cooling at a rate of 2–6°C/Ma for the middle crust of this part of the Grenville hinterland marked by protracted suprasolidus conditions for at least 70 Ma. It supports the definition of the Grenville Orogen as a large, hot, long‐duration orogen.